Positive electrode active material and preparation method thereof, electrode sheet, secondary battery and electrical device

By forming a cladding layer containing oxygen ion conductors and lithium ion conductors on the surface of the core material of the lithium-rich manganese-based positive electrode material, the problem of insufficient performance in secondary batteries is solved, and the first discharge efficiency, cycling performance and rate performance are significantly improved.

CN117941101BActive Publication Date: 2025-04-22CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280062469.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-08
Publication Date
2025-04-22
Estimated Expiration
2042-06-08

Smart Images

  • Figure CN117941101B_ABST
    Figure CN117941101B_ABST
Patent Text Reader

Abstract

The present application relates to a positive electrode active material and a preparation method thereof, a pole piece, a secondary battery and an electric device. The positive electrode active material comprises: a core material, comprising a lithium-rich manganese-based positive electrode material; a coating layer, coated on the outer surface of the core material, wherein the coating layer comprises an oxygen ion conductor and a lithium ion conductor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of secondary batteries, and specifically relates to a positive electrode active material and a preparation method thereof, a pole piece, a secondary battery and an electrical device. Background Art

[0002] Secondary batteries are widely used in various consumer electronic products and electric vehicles due to their outstanding features such as light weight, no pollution, and no memory effect.

[0003] With the increasing requirements for the energy density of power batteries, many positive electrode materials have been developed. For example, high-nickel ternary positive electrode materials, although they have high energy density, have extremely demanding requirements on preparation technology and storage environment. In contrast, lithium-rich manganese-based positive electrode materials are a type of positive electrode material that is highly anticipated. They have a high discharge specific capacity, almost twice that of lithium iron phosphate, and because they contain manganese, their preparation cost is relatively low. However, the first discharge efficiency, cycle performance, and rate performance of lithium-rich manganese-based positive electrode materials are poor, which greatly hinders their practical application. Summary of the invention

[0004] In view of the technical problems existing in the background technology, the present application provides a positive electrode active material, which is applied to a secondary battery and can improve the first discharge efficiency, cycle performance and rate performance of the secondary battery.

[0005] In order to achieve the above-mentioned object, the first aspect of the present application provides a positive electrode active material, comprising:

[0006] Core material, including lithium-rich manganese-based positive electrode material;

[0007] The coating layer is coated on the outer surface of the core material, and the coating layer contains an oxygen ion conductor and a lithium ion conductor.

[0008] Compared with the prior art, the present application at least has the following beneficial effects:

[0009] The positive electrode active material of the present application is formed on the outer surface of the core material containing the lithium-rich manganese-based positive electrode material, and the coating layer containing both the oxygen ion conductor and the lithium ion conductor is formed. The oxygen ion conductor and the lithium ion conductor are synergistically introduced as the coating layer of the core material containing the lithium-rich manganese-based positive electrode material. The interior of the oxygen ion conductor has a high oxygen vacancy concentration and has a high oxygen adsorption and storage capacity, which can effectively inhibit the release of lithium-rich manganese-based lattice oxygen, and at the same time reduce the escape of lithium ions, thereby improving the initial charge and discharge efficiency of the positive electrode active material. At the same time, the lattice oxygen release of the lithium-rich manganese-based positive electrode material is inhibited, and the structural stability of the lithium-rich manganese-based positive electrode material is improved, thereby improving the cycle stability of the positive electrode active material. At the same time, the introduction of a lithium ion conductor has a high ionic conductivity, improves the transmission rate of lithium ions, reduces the escape of lithium ions, and thereby improves the capacity and rate performance of the positive electrode active material.

[0010] In any embodiment of the present application, the oxygen ion conductor includes La 2 Mo 2 O 9 and at least one of a fluorite-type oxygen ion conductor.

[0011] In any embodiment of the present application, the fluorite-type oxygen ion conductor includes ZrO 2 、CeO 2 and GeO 2 At least one of .

[0012] In any embodiment of the present application, the lithium ion conductor comprises LiLaO 2 , Li 2 MoO 4 , Li 3 PO 4 , Li 3 BO 3 and LiTaO 3 At least one of .

[0013] In any embodiment of the present application, the oxygen ion conductor comprises La 2 Mo 2 O 9 ; The lithium ion conductor comprises LiLaO 2 and Li 2 MoO 4 .

[0014] In any embodiment of the present application, the molar ratio of lanthanum atoms to molybdenum atoms in the coating layer is 1:(1.02-1.1); optionally, it is 1:(1.02-1.05).

[0015] In any embodiment of the present application, the content of molybdenum atoms in the coating layer is 300-5000 ppm; and / or,

[0016] The content of lanthanum atoms in the coating layer is 500-5000ppm.

[0017] In any embodiment of the present application, the content of molybdenum atoms in the coating layer is 1000-4000 ppm; and / or,

[0018] The content of lanthanum atoms in the coating layer is 1000-3000ppm.

[0019] In any embodiment of the present application, the surface of the core material is doped with lanthanum atoms and molybdenum atoms.

[0020] In any embodiment of the present application, the surface thickness of the core material doped with lanthanum atoms and molybdenum atoms is not greater than 3 μm; it can be optionally not greater than 2 μm.

[0021] In any embodiment of the present application, the coating layer has a thickness of 0.01-4 μm.

[0022] In any embodiment of the present application, the coating layer has a thickness of 0.02-1 μm.

[0023] In any embodiment of the present application, the coating layer has 10 2 2- / IO 2- The peak intensity ratio is 0.5-1; it can be optionally 0.7-0.9;

[0024] Among them, IO 2 2- is the peak intensity of oxygen vacancies at 531 eV in X-ray photoelectron spectroscopy, IO 2- It corresponds to the peak intensity value of lattice oxygen of 529 eV in X-ray photoelectron spectroscopy test.

[0025] In any embodiment of the present application, the molecular formula of the lithium-rich manganese-based positive electrode material is xLi 2 MnO 3 ·(1-x)LiNi y Co z Mn a M 1-y-z-a O 2 ,

[0026] Among them, 0<x<1, 0≤y≤1, 0≤z≤1, 0≤a≤1, 0<y+z+a≤1; M is at least one of Mg, B, Al, V, Ti, Zr, Sn and Mo.

[0027] In any embodiment of the present application, the particle type of the lithium-rich manganese-based positive electrode material is secondary particles, single crystals or quasi-single crystals; and / or,

[0028] The specific surface area of ​​the lithium-rich manganese-based positive electrode material is less than 2.0 m 2 / g, optional 0.1-1m 2 / g;

[0029] The Dv50 particle size of the lithium-rich manganese-based positive electrode material is 1-20 μm, and can be optionally 3-15 μm.

[0030] The second aspect of the present application provides a method for preparing the positive electrode active material of the first aspect of the present invention, comprising the following steps:

[0031] The coating layer is formed on the surface of the core material.

[0032] In any embodiment of the present application, the oxygen ion conductor comprises La 2 Mo 2 O 9 , the lithium ion conductor comprises LiLaO 2 and Li 2 MoO 4 ; The preparation method comprises the following steps:

[0033] Molybdenum salt, lanthanum salt and lithium-rich manganese-based precursor are mixed in a solvent and subjected to hydrothermal reaction at 100-200°C for 8-12h to obtain a surface in-situ deposited La 2 Mo 2 O 9 Li-rich manganese-based precursor;

[0034] The surface is in situ deposited with La 2 Mo 2 O 9 The lithium-rich manganese-based precursor is mixed with a lithium salt and then calcined to obtain a positive electrode active material compositely coated with an oxygen ion conductor and a lithium ion conductor.

[0035] In any embodiment of the present application, the lithium-rich manganese-based precursor is Ni b Co c Mn d M (1-b-c-d) (OH) 2 ,

[0036] Wherein 0<b<0.4, 0≤c≤0.05, 0.6≤d<1, and M is at least one of Mg, B, Al, V, Ti, Zr, Sn and Mo.

[0037] In any embodiment of the present application, the solvent is at least one of water, ethanol, methanol and ethylene glycol; and / or,

[0038] The molybdenum salt is at least one of ammonium molybdate, sodium molybdate and potassium molybdate; and / or,

[0039] The lanthanum salt is at least one of lanthanum chloride and lanthanum nitrate; and / or,

[0040] The lithium salt is at least one of lithium carbonate, lithium hydroxide and lithium acetate; and / or,

[0041] The lithium element in the lithium salt and the La in situ deposited on the surface 2 Mo 2 O 9 The molar ratio of all metal elements in the lithium-rich manganese-based precursor is 1:(1.1-1.8), optionally 1:(1.1-1.5); and / or,

[0042] The pH value of the hydrothermal reaction is 8-10; and / or,

[0043] The calcination treatment atmosphere is air; and / or,

[0044] The calcination treatment step includes: pre-calcining at 300-500°C for 2-5h, and then sintering at 700-900°C for 10-20h.

[0045] The third aspect of the present application provides a positive electrode sheet, comprising:

[0046] A positive electrode current collector; and

[0047] A positive electrode active material layer, wherein the positive electrode active material layer is located on the surface of the positive electrode current collector, and the components of the positive electrode active material layer include the positive electrode active material provided in the first aspect of the present application or the positive electrode active material prepared by the preparation method provided in the second aspect of the present application.

[0048] The fourth aspect of the present application provides a secondary battery, comprising the positive electrode plate provided by the third aspect of the present application.

[0049] The fifth aspect of the present application provides an electrical device, comprising the secondary battery provided by the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0051] Figure 1 It is a schematic diagram of one embodiment of a secondary battery.

[0052] Figure 2 yes Figure 1 Exploded diagram of .

[0053] Figure 3 is a schematic diagram of one embodiment of a battery module.

[0054] Figure 4 is a schematic diagram of one embodiment of a battery pack.

[0055] Figure 5 yes Figure 4 Exploded diagram of .

[0056] Figure 6 It is a schematic diagram of one embodiment of an electric device using a secondary battery as a power source.

[0057] Description of reference numerals:

[0058] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module; 5. Secondary battery; 51. Shell; 52. Electrode assembly; 53. Cover plate; 6. Electrical device. DETAILED DESCRIPTION

[0059] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.

[0060] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.

[0061] In the description of this article, it should be noted that, unless otherwise specified, "above" and "below" are inclusive of the number itself, and "several" in "one or more" means two or more.

[0062] In the description herein, unless otherwise stated, the term "or" is inclusive. That is, the phrase "A or (or) B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist). Unless otherwise stated, the terms used in this application have the well-known meanings commonly understood by those skilled in the art. Unless otherwise stated, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).

[0063] Secondary battery

[0064] A secondary battery is a battery that can be recharged to activate the active materials after being discharged and continue to be used.

[0065] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet to play a role of isolation. The electrolyte plays a role of conducting ions between the positive electrode sheet and the negative electrode sheet.

[0066] Positive electrode

[0067] In a secondary battery, the positive electrode sheet generally includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material.

[0068] The positive electrode current collector may be a conventional metal foil or a composite current collector. A metal material may be disposed on a polymer substrate to form a composite current collector. As an example, the positive electrode current collector may be an aluminum foil.

[0069] As described in the background art, although lithium-rich manganese-based positive electrode materials have a high discharge specific capacity, their initial discharge efficiency, cycle performance and rate performance are poor, which greatly hinders their practical application.

[0070] After extensive research, the technical personnel of the present application found that the lithium-rich manganese-based positive electrode material is prone to oxygen release when the lithium-rich manganese-based positive electrode material is charged at a high voltage of more than 4.5V in the first cycle. At the same time, some lithium ions in the transition metal layer will react with O 2- Remove together to form Li 2O is released, and this part of the crystal vacancies is difficult to accept lithium ions in the subsequent charge and discharge process, resulting in a decrease in the initial charge and discharge efficiency of the lithium-rich manganese-based positive electrode material. At the same time, the formation of a large number of oxygen vacancies inside the lithium-rich manganese-based positive electrode material easily leads to the migration of transition metal ions in the lithium-rich manganese-based positive electrode material, causing the crystal structure to rearrange and cause the instability of the structure of the lithium-rich manganese-based positive electrode material, thereby causing the cycle performance to deteriorate. In addition, due to the low electronic and ionic conductivity of the lithium-rich manganese-based positive electrode itself, and the intensified side reaction between the surface of the lithium-rich manganese-based positive electrode and the electrolyte under high voltage, the rate performance of the lithium-rich manganese-based positive electrode is extremely poor.

[0071] Based on this, an embodiment of the present application provides a positive electrode active material, which includes a core material and a coating layer. The core material includes a lithium-rich manganese-based positive electrode material. The coating layer is coated on the outer surface of the core material, and the coating layer includes an oxygen ion conductor and a lithium ion conductor.

[0072] Without wishing to be limited to any theory, the positive electrode active material of the present application is formed by forming the above-mentioned coating layer containing both oxygen ion conductor and lithium ion conductor on the outer surface of the core material containing lithium-rich manganese-based positive electrode material. The oxygen ion conductor and the lithium ion conductor are synergistically introduced as the coating layer of the core material containing lithium-rich manganese-based positive electrode material. The interior of the oxygen ion conductor has a high oxygen vacancy concentration and has high oxygen adsorption and storage capacity, which can effectively inhibit the release of lithium-rich manganese-based lattice oxygen, and at the same time reduce the escape of lithium ions, thereby improving the initial charge and discharge efficiency of the positive electrode active material. At the same time, the lattice oxygen release of the lithium-rich manganese-based positive electrode material is suppressed, and the structural stability of the lithium-rich manganese-based positive electrode material is improved, thereby improving the cycle stability of the positive electrode active material. At the same time, the introduction of a lithium ion conductor has a high ionic conductivity, improves the transmission rate of lithium ions, reduces the escape of lithium ions, and thereby improves the capacity and rate performance of the positive electrode active material.

[0073] The components in the positive electrode active material layer of the positive electrode plate include the above-mentioned coated positive electrode active material.

[0074] After in-depth research, the technical personnel of the present application found that when the positive electrode active material of the present application satisfies the above-mentioned design conditions and optionally satisfies one or more of the following conditions, the performance of the secondary battery can be further improved.

[0075] In some embodiments, oxygen ion conductors include, but are not limited to: La 2 Mo 2 O 9 and at least one of a fluorite-type oxygen ion conductor. Further, the fluorite-type oxygen ion conductor includes ZrO 2 、CeO 2 and GeO 2 At least one of .

[0076] In some embodiments, lithium ion conductors include, but are not limited to: LiLaO 2 , Li 2 MoO 4 , Li 3 PO 4 , Li 3 BO 3 and LiTaO 3 At least one of .

[0077] In some embodiments, the lithium ion conductor comprises LiLaO 2 and Li 2 MoO 4 The combination of two specific lithium ion conductors can significantly improve the ionic conductivity of the positive electrode material, while also effectively inhibiting the cation mixing and Mn 3+ In some embodiments, the oxygen ion conductor comprises La 2 Mo 2 O 9 , lithium ion conductors include LiLaO 2 and Li 2 MoO 4 Since the oxygen ion conductor and the lithium ion conductor have the same elements, this particular combination will have good compatibility between the two, so that the oxygen ions and lithium ion conductors in the coating layer are more closely combined, which is beneficial to improving the stability of the coating layer itself and the rapid conduction of ions.

[0078] Furthermore, the molar ratio of lanthanum atoms to molybdenum atoms in the coating layer is 1:(1.02-1.1); more preferably 1:(1.02-1.05). By controlling the molar ratio of molybdenum to lanthanum in the coating layer, it is possible to ensure the synthesis of stoichiometric lanthanum molybdate.

[0079] Further, the content of molybdenum atoms in the coating layer is 300-5000ppm, and can be 1000-4000ppm. Further, the content of lanthanum atoms in the coating layer is 500-5000ppm; and can be 1000-3000ppm. Controlling the content of molybdenum atoms and lanthanum atoms in the coating layer can ensure that the coating layer is not too thick, which affects the capacity of the positive electrode active material, thereby achieving a better coating effect.

[0080] It can be understood that when La is formed in situ on the surface of the core material 2 Mo 2 O 9When the core material is doped with lanthanum atoms and molybdenum atoms, the surface of the core material is doped with lanthanum atoms and molybdenum atoms. Further, the surface thickness of the core material doped with lanthanum atoms and molybdenum atoms is not greater than 3 μm; optionally, it can be not greater than 2 μm. Further optionally, the surface thickness of the core material doped with lanthanum atoms and molybdenum atoms is not greater than 1 μm, for example, the doping thickness is 0.1 μm-1 μm, 0.1 μm-0.6 μm.

[0081] In some embodiments, the coating layer has a thickness of 0.01-4 μm, such as 0.01 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 2 μm, 3 μm, 4 μm. Preferably, the coating layer has a thickness within a given range to avoid the problem that the coating layer is too thick, which affects the ion conductivity and coating uniformity of the core material, thereby causing the capacity of the positive electrode active material to be reduced. It can also avoid the problem that the coating layer is too thin and the improvement effect is not obvious, thereby further improving the first discharge efficiency, cycle performance and rate performance of the positive electrode active material.

[0082] Optionally, the thickness of the coating layer is 0.01-1 μm; further optionally, 0.02-0.5 μm. For example, the oxygen ion conductor contains La 2 Mo 2 O 9 , lithium ion conductors include LiLaO 2 and Li 2 MoO 4 When the coating layer is used, the thickness of the coating layer may be selected to be 0.01-1 μm; further selected to be 0.02-0.5 μm.

[0083] In some embodiments, the coating layer IO 2 2- / IO 2- The peak intensity ratio is 0.5-1; it can be 0.7-0.9; among which, IO 2 2- is the peak intensity of oxygen vacancies at 531 eV in X-ray photoelectron spectroscopy, IO 2- corresponds to the peak intensity of lattice oxygen at 529 eV in the X-ray photoelectron spectroscopy test. 2 2- / IO 2- The peak intensity ratio is within a given range, so that there is an appropriate amount of oxygen vacancies in the coating layer, which can effectively inhibit the oxygen release of the material, improve the structural stability of the lithium-rich manganese-based positive electrode material in the positive electrode active material, and inhibit the phase change of the lithium-rich manganese-based positive electrode material.

[0084] In some embodiments, the molecular formula of the lithium-rich manganese-based positive electrode material is xLi 2 MnO 3 ·(1-x)LiNiy Co z Mn a M 1-y-z-a O 2 ,

[0085] Where 0<x<1, 0≤y≤1, 0≤z≤1, 0≤a≤1, 0<y+z+a≤1; M is Mg, B, Al, V, Ti, Zr, Sn and M o The coating layer can be applied to the above-mentioned lithium-rich manganese-based positive electrode material to improve its first discharge efficiency, cycle performance and rate performance.

[0086] Optionally, the lithium-rich manganese-based positive electrode material includes but is not limited to the following types: 0.35Li 2 MnO 3 0.65LiNi 0.46 Co 0.08 Mn 0.46 O 2 、0.35Li 2 MnO 3 0.65LiNi 0.45 Co 0.08 Mn 0.46 Mg 0.01 O 2 、0.35Li 2 MnO 3 0.65LiNi 0.45 Co 0.08 Mn 0.46 Al 0.01 O 2 、0.35Li 2 MnO 3 .0.65LiNi 0.45 Co 0.08 Mn 0.46 Ti 0.01 O 2 、0.35Li 2 MnO 3 0.65LiNi 0.45 Co 0.08 Mn 0.46 V 0.01 O 2 .

[0087] It is understood that in some embodiments, the core material is the above-mentioned lithium-rich manganese-based positive electrode material. In other embodiments, the core material may contain other positive electrode materials commonly used in the art in addition to the above-mentioned lithium-rich manganese-based positive electrode material.

[0088] In some embodiments, the particle type of the lithium-rich manganese-based positive electrode material is secondary particles, single crystals or quasi-single crystals, wherein the secondary particles refer to secondary spherical particles formed by agglomeration of primary particles.

[0089] In some embodiments, the specific surface area of ​​the lithium-rich manganese-based positive electrode material is less than 2.0 m 2 / g, optional 0.1-1m 2 / g.

[0090] In some embodiments, the Dv50 particle size of the lithium-rich manganese-based positive electrode material is 1-20 μm; optionally 3-15 μm.

[0091] The lithium-rich manganese-based positive electrode material used in the core material of the present application has a regular morphology, uniform particle size distribution, and a low specific surface area, so it can have a higher compaction density, thereby ensuring that the secondary battery prepared has a higher energy density and excellent cycle performance.

[0092] The above-mentioned positive electrode active material may also optionally include a binder, a conductive agent and other optional auxiliary agents.

[0093] As an example, the conductive agent may be one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, Super P (SP), graphene, and carbon nanofibers.

[0094] As an example, the binder can be one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).

[0095] The present application also provides a method for preparing the above-mentioned positive electrode active material, comprising the following steps: forming the above-mentioned coating layer on the surface of the above-mentioned core material.

[0096] It is understandable that the coating layer can be formed by using techniques commonly used in the art, such as solid phase coating, spraying, in-situ deposition, and the like.

[0097] In some embodiments, the oxygen ion conductor comprises La 2 Mo 2 O 9 , lithium ion conductors include LiLaO 2 and Li 2 MoO 4 ; Preferably, the preparation method thereof includes the following steps S11-S12.

[0098] Step S11: Molybdenum salt, lanthanum salt and lithium-rich manganese-based precursor are mixed in a solvent and subjected to hydrothermal reaction at 100-200° C. for 8-12 hours to obtain a surface in-situ deposited La 2 Mo 2 O 9 Li-rich manganese-based precursor.

[0099] Step S12: La is deposited in situ on the surface 2 Mo 2 O 9 The lithium-rich manganese-based precursor is mixed with a lithium salt and then calcined to obtain a positive electrode active material compositely coated with an oxygen ion conductor and a lithium ion conductor.

[0100] Thus, through the calcination step of step S12, part of La 2 Mo 2 O 9 Reacts with some lithium salts to form LiLaO 2 and Li 2 MoO 4 As a lithium ion conductor, part of La 2 Mo 2 O 9 On the other hand, the lithium-rich manganese-based precursor can be converted into a lithium-rich manganese-based positive electrode material by reacting with lithium salts and making La 2 Mo 2 O 9 Some of the lanthanum and molybdenum metal ions in the material are doped into the surface layer of the lithium-rich manganese-based positive electrode material.

[0101] The preparation method described above in the present application can synthesize a lithium-rich manganese-based material compositely coated with an oxygen ion conductor and a lithium ion conductor, wherein the oxygen ion conductor contains La 2 Mo 2 O 9 , lithium ion conductors include LiLaO 2 and Li 2 MoO 4 , so that the positive electrode active material has excellent first discharge efficiency, cycle performance and rate performance.

[0102] In some embodiments, the lithium-rich manganese-based precursor is Ni b Co c Mn d M (1-b-c - d) (OH) 2 .

[0103] Wherein, 0<b<0.4, 0≤c≤0.05, 0.6≤d<1, and M is at least one of Mg, B, Al, V, Ti, Zr, Sn and Mo. The Mn content in the lithium-rich manganese-based precursor is high and the Co content is low, which is beneficial to reduce the cost. At the same time, the lithium-rich manganese-based precursor can be doped in the above preparation process, which is beneficial to doping the doped metal ions into the lattice during the sintering process and improving the structural stability of the positive electrode active material.

[0104] Optionally, the lithium-rich manganese-based precursor includes but is not limited to the following types: Ni 0.30 Co 0.05 Mn 0 . 65 (OH) 2 、Ni 0.29 Co 0.05 Mn 0.65 Mg 0.01 (OH) 2 、Ni 0.29 Co 0.05 Mn 0.65 Al 0.01 (OH) 2 、Ni 0.29 Co 0.05 Mn 0.65 Ti 0.01 (OH) 2 、Ni 0.29 Co 0.05 Mn 0.65 V 0.01 (OH) 2 .

[0105] In some embodiments, the solvent is at least one of water, ethanol, methanol and ethylene glycol.

[0106] In some embodiments, the molybdenum salt is at least one of ammonium molybdate, sodium molybdate, and potassium molybdate.

[0107] In some embodiments, the lanthanum salt is at least one of lanthanum chloride and lanthanum nitrate.

[0108] In some embodiments, the lithium salt is at least one of lithium carbonate, lithium hydroxide and lithium acetate.

[0109] Furthermore, in step S12, the lithium element in the lithium salt and the La in situ deposited on the surface 2 Mo 2 O 9The molar ratio of all metal elements in the lithium-rich manganese-based precursor is 1: (1.1-1.8), which can be optionally 1: (1.1-1.5). Among them, all metal elements include Ni, Co, Mn, M, Mo and La. In this way, it can be ensured that the lithium salt added in step S12 can not only meet the lithium required by the lithium-rich manganese-based precursor to form a lithium-rich manganese-based positive electrode material, but also meet the surface La 2 Mo 2 O 9 Partial reaction to form LiLaO 2 and Li 2 MoO 4 Lithium required.

[0110] Furthermore, the pH value of the hydrothermal reaction is 8-10.

[0111] Furthermore, the calcination treatment is carried out in air.

[0112] Furthermore, the calcination treatment step includes: pre-calcining at 300-500°C for 2-5h, and then sintering at 700-900°C for 10-20h.

[0113] The preparation method has a simple process, and the prepared positive electrode active material has good first discharge efficiency, cycle performance and rate performance.

[0114] Negative electrode

[0115] In a secondary battery, the negative electrode plate generally includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.

[0116] The negative electrode current collector may be a conventional metal foil or a composite current collector, for example, a metal material may be disposed on a polymer substrate to form a composite current collector. As an example, the negative electrode current collector may be a copper foil.

[0117] Commonly used negative electrode active materials include, but are not limited to, one or more of artificial graphite, natural graphite, hard carbon materials, soft carbon, silicon-based materials and tin-based materials. The silicon-based material can be selected from one or more of elemental silicon, silicon oxide compounds, such as silicon monoxide, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material can be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. These materials can all be obtained commercially. In some embodiments, in order to further improve the energy density of the battery, the negative electrode active material includes a silicon-based material.

[0118] Isolation film

[0119] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0120] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0121] Electrolyte

[0122] The secondary battery may include an electrolyte that conducts ions between the positive electrode and the negative electrode. The electrolyte may include an electrolyte salt and a solvent.

[0123] As an example, the electrolyte salt may be selected from lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO 2 F 2 ), one or more of lithium difluorobis(oxalate) phosphate (LiDFOP) and lithium tetrafluorooxalate phosphate (LiTFOP).

[0124] As an example, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0125] In some embodiments, the electrolyte further includes additives, such as additives that may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.

[0126] In some embodiments, the secondary battery of the present application is a lithium ion secondary battery.

[0127] Secondary batteries can be prepared according to conventional methods in the art, for example, the positive electrode sheet, the separator, and the negative electrode sheet are wound (or stacked) in sequence, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, to obtain a battery cell, the battery cell is placed in an outer package, the electrolyte is injected and the package is sealed to obtain a secondary battery.

[0128] The embodiment of the present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0129] In some embodiments, the secondary battery may include an outer package for packaging a positive electrode sheet, a negative electrode sheet, and an electrolyte.

[0130] In some embodiments, reference Figure 2 The outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity.

[0131] The positive electrode sheet, the negative electrode sheet and the separator can be wound or laminated to form an electrode assembly 52. ​​The electrode assembly 52 is encapsulated in the housing cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to needs.

[0132] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.

[0133] In some embodiments, secondary batteries may be assembled into a battery module. The battery module may contain multiple secondary batteries, and the specific number may be adjusted according to the application and capacity of the battery module.

[0134] Figure 3The battery module 4 is used as an example. In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0135] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0136] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0137] Figure 4 and Figure 5 The battery pack 1 is taken as an example. The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0138] Electrical devices

[0139] The present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack. The secondary battery, battery module, or battery pack can be used as a power source for the device, or as an energy storage unit for the device. The device can be, but is not limited to, a mobile device such as a mobile phone, a laptop computer, or an electric vehicle such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, or an electric train, a ship, a satellite, an energy storage system, etc.

[0140] The device can select a secondary battery, a battery module or a battery pack according to its usage requirements.

[0141] Figure 6 The power-consuming device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the high power and high energy density requirements of the device for the secondary battery, a battery pack or a battery module can be used.

[0142] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0143] The beneficial effects of the present application are further illustrated below in conjunction with embodiments. Specific embodiments

[0145] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the following will be further described in detail with reference to the embodiments and drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work belong to the scope of protection of the present application.

[0146] The materials used in the examples of this application can all be obtained commercially.

[0147] 1. Preparation and performance testing of positive electrode active materials

[0148] 1. Preparation of positive electrode active materials

[0149] Positive electrode active material 1-5

[0150] S1: uniformly dispersing the lithium-rich manganese-based precursor in a solvent, and then dissolving a molybdenum salt (ammonium molybdate) and a lanthanum salt (lanthanum nitrate) in the solvent to prepare a solution;

[0151] S2: under water bath conditions, the molybdenum salt (ammonium molybdate) and lanthanum salt (lanthanum nitrate) solutions in step S1 are added dropwise to the dispersion of the precursor and the pH of the solution is adjusted to 9. The solution is then stirred at room temperature for 4 hours and then transferred to a reactor for hydrothermal reaction at 100-200°C for 8-12 hours. After the reactor is cooled to room temperature, the molybdenum salt and the lanthanum salt are reacted to form lanthanum molybdate (La 2 Mo 2 O 9 ) is in-situ deposited onto the surface of the precursor;

[0152] S3: The precursor product obtained in step S2 is washed with deionized water and vacuum dried, then ball-milled with lithium salt (lithium carbonate), pre-calcined at 300-500°C for 2h, then sintered at 700-900°C for 10-20h, and naturally cooled to room temperature to obtain a surface-coated lithium-rich manganese-based positive electrode material. The surface of the lithium-rich manganese-based positive electrode material is coated with an oxygen ion conductor La 2 Mo 2 O 9 and lithium ion conductor LiLaO 2 and Li 2 MoO 4 The specific parameters are shown in Table 1.

[0153] Note: Li / Me in Table 1 refers to the molar ratio of lithium element in the lithium salt (lithium carbonate) added in step S3 to all metal elements in the precursor product added in step S3. It can be understood that the amount of all metal elements in the precursor product added in step S3 can be obtained by element testing.

[0154] 2. Performance test of positive electrode active materials

[0155] 1) Molecular structure and Dv50 particle size test of core material.

[0156] Dv50 refers to the particle size corresponding to 50% in the volume distribution. As an example, Dv50 can be conveniently measured by referring to GB / T19077-2016 particle size distribution laser diffraction method using a laser particle size analyzer, such as the Mastersizer 2000E laser particle size analyzer of Malvern Instruments Ltd., UK.

[0157] 2) The thickness test of Mo and La doping into the core material, referred to as doping thickness in Table 1.

[0158] The thickness of Mo and Lanthanum doped into the core material can be characterized by well-known ion polishing cross-sectional (CP) elemental surface scanning and line scanning analysis.

[0159] 3) La:Mo molar ratio test of coating layer, La and Mo content test, IO 2 2- / IO 2- test.

[0160] The La:Mo molar ratio of the coating layer and the content of La and Mo can be tested by using a known X-ray energy dispersive spectrometer (EDS) for surface scanning analysis and an inductively coupled plasma atomic emission spectrometer (ICP-AES) for testing and analysis. 2 2- / IO 2- The well-known X-ray photoelectron spectroscopy (XPS) can be used for analysis, wherein IO 2 2- is the peak intensity of oxygen vacancies at 531 eV in X-ray photoelectron spectroscopy, IO 2- It corresponds to the peak intensity value of lattice oxygen of 529 eV in X-ray photoelectron spectroscopy test.

[0161] Some raw materials and performance test results of positive electrode active materials 1-5 are shown in Table 1 below:

[0162] The thickness of the coating layer is the total thickness of all coating layers.

[0163] Table 1

[0164]

[0165] Among them, core materials 1-5 are 0.35Li 2 MnO 3 0.65LiNi 0.46 Co 0.08 Mn 0.46 O 2 、0.35Li 2 MnO 3 0.65LiNi 0.45 Co 0.08 Mn 0.46 Mg 0.01 O 2 、0.35Li 2 MnO 3 0.65LiNi 0.45 Co 0.08 Mn 0.46 Al 0.01 O 2 、0.35Li 2 MnO 3 0.65LiNi 0.45 Co 0.08 Mn 0.46 Ti 0.01 O 2 、0.35Li 2 MnO 3 0.65LiNi 0.45 Co 0.08 Mn 0.46 V 0.01 O 2 .

[0166] Embodiment 6:

[0167] The lithium-rich manganese-based cathode material 0.35Li 2 MnO 3 0.65LiNi 0.45 Co 0.08 Mn 0.46 Al 0.01 O 2 and oxygen ion conductor La 2 Mo 2 O 9 and lithium ion conductor LiLaO 2 Solid phase mixing is performed, and after the mixing is completed, pre-calcination is performed at 400° C. for 2 hours in an air atmosphere, and then the temperature is kept at 800° C. for 12 hours to obtain a modified lithium-rich manganese-based positive electrode material;

[0168] In Examples 7-13, except for changing the composition of each raw material as shown in Table 2, the same preparation method as in Example 6 was adopted.

[0169] The performance test results of positive electrode active materials 6-13 are shown in Table 2 below:

[0170] Table 2

[0171]

[0172] 2. Preparation of positive electrode sheet

[0173] Positive electrode 1-13

[0174] The positive electrode active materials 1-13, conductive carbon black (SP), and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96.8:2.2:1, dissolved in N-methylpyrrolidone (NMP), and the positive electrode slurry is coated on a 400 mm wide aluminum foil, dried, cold pressed, and cut to obtain positive electrode sheets.

[0175] 3. Preparation of batteries

[0176] 1. Positive electrode sheet: Use the positive electrode sheet 1-13 prepared above.

[0177] 2. Separator: Use polyethylene (PE) porous polymer separator as separator

[0178] 3. Negative electrode sheet: Graphite, binder styrene butadiene rubber (SBR), binder polyacrylic acid (PAA), dispersant (CMC-Na), conductive carbon black (Super-P, SP), and carbon nanotubes (CNT) are fully stirred and mixed in an appropriate amount of deionized water at a weight ratio of 95%: 2%: 1%: 1%: 0.7%: 0.3% to prepare a negative electrode slurry. The negative electrode slurry is then coated on a 6μm thick copper foil, dried and cold pressed to form a negative electrode active material layer, and cut into negative electrode sheets.

[0179] 4. Electrolyte: After mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) at a volume ratio of 3:6:1, fully dried lithium salt (LiPF6) is dissolved in a mixed organic solvent at a ratio of 1 mol / L to obtain the desired electrolyte.

[0180] 5. Full battery assembly: stack the above-mentioned positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive and negative electrodes to play a role of isolation, and wind them to obtain a bare cell. Place the bare cell in an outer packaging aluminum shell, inject the above-prepared electrolyte into the dry cell after high-temperature drying, and obtain lithium-ion secondary batteries 1-13 after vacuum packaging, standing, formation, shaping, etc., as shown in Table 3.

[0181] 4. Battery Performance Evaluation

[0182] The performance evaluation of each of Batteries 1 to 13 was carried out in the following manner.

[0183] 1. First discharge efficiency

[0184] The injected battery 1-13 was charged to 3.4V at a constant current of 0.02C at 45°C, allowed to stand for 5 minutes, and then charged to 3.75V at a constant current of 0.1C, with the capacity recorded as Z1. The battery was then vented and re-sealed. The double-sealed battery was placed at 25°C, charged to 4.5V at a constant current of 0.33C, and then charged to 0.02C at a constant voltage, allowed to stand for 5 minutes, with the capacity recorded as Z2. The battery was then discharged to 2.0V at 0.33C, with the capacity recorded as D1.

[0185] The calculation formula for the first efficiency is as follows: first efficiency = D1 / (Z1+Z2).

[0186] 2. Discharge capacity test

[0187] Under a constant temperature environment of 25°C, at 2.0V-4.5V, charge to 4.5V at 0.33C, then charge at a constant voltage at 4.5V to a current of 0.05C, let stand for 5 minutes, then discharge to 2.0V at 0.33C, and record the specific capacity result of the lithium ion battery at the 0.33C discharge rate (i.e., 0.33C discharge capacity); let stand for 5 minutes, charge to 4.5V at 0.33C, then charge at a constant voltage at 4.5V to a current of 0.05C, let stand for 5 minutes, then discharge to 2.0V at 0.5C, and record the specific capacity result of the lithium ion battery at the 0.5C discharge rate (i.e., 0.5C discharge capacity).

[0188] 3. Cycle performance test:

[0189] 1) Under a constant temperature environment of 25°C, the first charge and discharge were performed, and constant current and constant voltage charging (charging to a current of 0.05C) was performed at a charging current of 0.5C (i.e., the current value at which the theoretical capacity is completely discharged within 2 hours) until the upper limit voltage reached 4.46V. After standing for 5 minutes, constant current discharge was performed at a discharge current of 0.5C until the final voltage was 2.3V, and the discharge capacity of the first cycle was recorded; then continuous charge and discharge cycles were performed.

[0190] The capacity retention rate of 500 cls of full electric cycle at 25°C, that is, the capacity retention rate of the 500th cycle = (discharge capacity of the 500th cycle / discharge capacity of the first cycle) × 100%.

[0191] 2) Under a constant temperature environment of 45°C, the first charge and discharge were carried out, and constant current and constant voltage charging (charging to a current of 0.05C) was carried out at a charging current of 0.5C (i.e., the current value at which the theoretical capacity is completely discharged within 2 hours) until the upper limit voltage reached 4.46V. After standing for 5 minutes, constant current discharge was carried out at a discharge current of 0.5C until the final voltage was 2.3V, and the discharge capacity of the first cycle was recorded; then continuous charge and discharge cycles were carried out.

[0192] The capacity retention rate of 500 cls of full electric cycle at 45°C, that is, the capacity retention rate of the 500th cycle = (discharge capacity of the 500th cycle / discharge capacity of the first cycle) × 100%.

[0193] Table 3

[0194]

[0195] It can be seen from Table 3 that the coating layer of the positive electrode active material in Comparative Example 1 does not contain an oxygen ion conductor, the coating layer of Comparative Example 2 does not contain a lithium ion conductor, and the coating layer of the positive electrode active material in each embodiment contains both an oxygen ion conductor and a lithium ion conductor; compared with the comparative examples, the secondary batteries prepared in each embodiment have better first discharge efficiency, cycle performance and rate performance.

[0196] Furthermore, it can be seen from Examples 1-5 and Examples 6-11 that the secondary batteries prepared by using specific types of oxygen ion conductors and lithium ion conductors in Examples 1-5 can simultaneously have better first discharge efficiency, cycle performance and rate performance.

[0197] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A positive electrode active material, characterized in that: Comprising: A core material containing a lithium-rich manganese-based cathode material; A coating layer coated on the outer surface of the core material, the coating layer contains an oxygen ion conductor and a lithium ion conductor, the coating layer contains lanthanum atoms and molybdenum atoms, the content of molybdenum atoms in the coating layer is 300-5000 ppm, and the content of lanthanum atoms in the coating layer is 500-5000 ppm.

2. The positive electrode active material according to claim 1, characterized in that The oxygen ion conductor contains La2Mo2O9; the lithium ion conductor contains LiLaO2 and Li2MoO4.

3. The positive electrode active material according to claim 2, characterized in that The molar ratio of lanthanum atoms to molybdenum atoms in the coating layer is 1:(1.02-1.1).

4. The positive electrode active material according to claim 3, characterized in that The molar ratio of lanthanum atoms to molybdenum atoms in the coating layer is 1:(1.02-1.05).

5. The positive electrode active material according to any one of claims 1 to 4, characterized in that The content of molybdenum atoms in the coating layer is 1000-4000 ppm; and / or, The content of lanthanum atoms in the coating layer is 1000-3000 ppm.

6. The positive electrode active material according to any one of claims 2 to 4, characterized in that The surface of the core material is doped with lanthanum atoms and molybdenum atoms.

7. The positive electrode active material according to claim 6, characterized in that The surface thickness of the core material doped with lanthanum atoms and molybdenum atoms is not greater than 3 μm.

8. The positive electrode active material according to claim 7, characterized in that The surface thickness of the core material doped with lanthanum atoms and molybdenum atoms is not greater than 2 μm.

9. The positive electrode active material according to any one of claims 1 to 4, characterized in that The thickness of the coating layer is 0.01-4 μm.

10. The positive electrode active material according to any one of claims 1 to 4, characterized in that The thickness of the coating layer is 0.02-1 μm.

11. The positive electrode active material according to any one of claims 1 to 4, characterized in that IO2 in the coating layer 2- / IO 2- The peak intensity ratio is 0.5-1; Among them, IO2 2- is the peak intensity of oxygen vacancies at 531 eV in X-ray photoelectron spectroscopy, IO 2- It corresponds to the peak intensity value of lattice oxygen of 529 eV in X-ray photoelectron spectroscopy test.

12. The positive electrode active material according to claim 11, characterized in that IO2 in the coating layer 2- / IO 2- The peak intensity ratio is 0.7-0.

9.

13. The positive electrode active material according to any one of claims 1 to 4, characterized in that The molecular formula of the lithium-rich manganese-based positive electrode material is xLi2MnO3·(1-x)LiNi y Co z Mn a M 1-y-z-a O2, Where 0 < x < 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ a ≤ 1, 0 < y + z + a ≤ 1; M is at least one of Mg, B, Al, V, Ti, Zr, Sn and Mo.

14. The positive electrode active material according to any one of claims 1 to 4, characterized in that The particle type of the lithium-rich manganese-based cathode material is secondary particles, single crystal or quasi-single crystal; and / or, The specific surface area of ​​the lithium-rich manganese-based positive electrode material is less than 2.0 m 2 / g; The Dv50 particle size of the lithium-rich manganese-based cathode material is 1-20 μm.

15. The positive electrode active material according to claim 14, characterized in that The specific surface area of ​​the lithium-rich manganese-based positive electrode material is 0.1-1 m 2 / g; The Dv50 particle size of the lithium-rich manganese-based cathode material is 3-15 μm.

16. A method for preparing a positive electrode active material according to any one of claims 1 to 15, characterized in that: Including the following steps: Forming the coating layer on the surface of the core material.

17. The preparation method according to claim 16, characterized in that: The oxygen ion conductor contains La2Mo2O9, the lithium ion conductor contains LiLaO2 and Li2MoO4; the preparation method includes the following steps: Mixing a molybdenum salt, a lanthanum salt and a lithium-rich manganese-based precursor in a solvent, and performing a hydrothermal reaction at 100-200 °C for 8-12 h to obtain a lithium-rich manganese-based precursor with La2Mo2O9 in-situ deposited on the surface; Mixing the lithium-rich manganese-based precursor with La2Mo2O9 in-situ deposited on the surface with a lithium salt, and then performing a calcination treatment to obtain a cathode active material with a composite coating of an oxygen ion conductor and a lithium ion conductor.

18. The preparation method according to claim 17, characterized in that: The lithium-rich manganese-based precursor is Ni b Co c Mn d M (1-b-c-d) (OH)2, Where 0 < b < 0.4, 0 ≤ c ≤ 0.05, 0.6 ≤ d < 1, M is at least one of Mg, B, Al, V, Ti, Zr, Sn and Mo.

19. The preparation method according to any one of claims 17 to 18, characterized in that: The solvent is at least one of water, ethanol, methanol and ethylene glycol; and / or, The molybdenum salt is at least one of ammonium molybdate, sodium molybdate and potassium molybdate; and / or, The lanthanum salt is at least one of lanthanum chloride and lanthanum nitrate; and / or, The lithium salt is at least one of lithium carbonate, lithium hydroxide and lithium acetate; and / or, The molar ratio of lithium element in the lithium salt to all metal elements in the lithium-rich manganese-based precursor with La2Mo2O9 in-situ deposited on the surface is 1:(1.1-1.8); and / or, The pH value of the hydrothermal reaction is 8-10; and / or, The calcination atmosphere is air; and / or, The calcination treatment step includes: pre-calcining at 300-500°C for 2-5h, and then sintering at 700-900°C for 10-20h.

20. The preparation method according to claim 19, characterized in that: The molar ratio of the lithium element in the lithium salt to all the metal elements in the lithium-rich manganese-based precursor with La2Mo2O9 in-situ deposited on the surface is 1:(1.1-1.5).

21. A positive electrode sheet, characterized in that: include: Positive electrode current collector; and A positive electrode active material layer, wherein the positive electrode active material layer is located on the surface of the positive electrode current collector, and the components of the positive electrode active material layer include the positive electrode active material according to any one of claims 1 to 15 or the positive electrode active material prepared by the preparation method according to any one of claims 16 to 20.

22. A secondary battery, characterized in that: Comprising the positive electrode sheet as described in claim 21.

23. An electrical device, characterized in that: Includes a secondary battery selected from the group consisting of those described in claim 22.

Citation Information

Patent Citations

  • Doped lithium cobaltate having composite cladding layer and preparation method and application thereof

    CN109256531A

  • Coating method for effectively inhibiting oxygen loss of lithium-enriched magnesium-based positive electrode material

    CN109560265A

  • Modified lithium-rich manganese-based positive electrode material and preparation method thereof

    CN113823786A